How one TSH receptor antibody induces thyrocyte proliferation while another induces apoptosis - Morshed, Syed A. (2013)
Thyroid stimulating hormone (TSH) activates two major G-protein arms, Gsα and Gq leading to initiation of down-stream signaling cascades for survival, proliferation and production of thyroid hormones. Antibodies to the TSH receptor (TSHR-Abs), found in patients with Graves’ disease, may have stimulating, blocking, or neutral actions on the thyroid cell. We have shown previously that such TSHR-Abs are distinct signaling imprints after binding to the TSHR and that such events can have variable functional consequences for the cell. In particular, there is a great contrast between stimulating (S) TSHR-Abs, which induce thyroid hormone synthesis and secretion as well as thyroid cell proliferation, compared to so called “neutral” (N) TSHR-Abs which may induce thyroid cell apoptosis via reactive oxygen species (ROS) generation. In the present study, using a rat thyrocyte (FRTL-5) ex vivo model system, our hypothesis was that while N-TSHR-Abs can induce apoptosis via activation of mitochondrial ROS (mROS), the S-TSHR-Abs are able to stimulate cell survival and avoid apoptosis by actively suppressing mROS. Using fluorescent microscopy, fluorometry, live cell imaging, immunohistochemistry and immunoblot assays, we have observed that S-TSHR-Abs do indeed suppress mROS and cellular stress and this suppression is exerted via activation of the PKA/CREB and AKT/mTOR/S6K signaling cascades. Activation of these signaling cascades, with the suppression of mROS, initiated cell proliferation. In sharp contrast, a failure to activate these signaling cascades with increased activation of mROS induced by N-TSHR-Abs resulted in thyroid cell apoptosis. Our current findings indicated that signaling diversity induced by different TSHR-Abs regulated thyroid cell fate. While S-TSHR-Abs may rescue cells from apoptosis and induce thyrocyte proliferation, N-TSHR-Abs aggravate the local inflammatory infiltrate within the thyroid gland, or in the retro-orbit, by inducing cellular apoptosis; a phenomenon known to activate innate and by-stander immune-reactivity via DNA release from the apoptotic cells.